Becoming a global citizen?: Developing community-facing learning in the social sciences. Issue 1 (1st March 2021) - Booth, Jane
Abstract: This article will propose a more authentic learning environment for students of the social sciences, one that is not only learner-centred but community-centred. Drawing on the principles of social pedagogy, cultural-based learning, place-based learning and co-production, this article advocates engaging community groups as co-producers in the generation of knowledge, enhancing learning within – and beyond – the university. By not using the community simply as a source of research data or placement opportunities, the curriculum is more likely to produce reflexive graduates better equipped to engage with complex global problems, enhancing their global citizenship and that of the wider community.